EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL MEDIASI ANTARA TALENT MANAGEMENT, KNOWLEDGE SHARING DAN EMPLOYEE CAPABILITY - Kalista Sabbatho; Sri Mintarti; Tetra Hidayati (Derivatif : Jurnal Manajemen, 2020)
The purpose of this study was to test out the effect of talent management and knowledge sharing on employee capability with employee management as the mediation variable for the State Civil Apparatus (ASN) within the Secretariat environment of Mahakam Ulu Regency. This study is a quantitative study that was expected to be able to measure the effect of the variables. The data collection was conducted using a questionnaire with a saturated sampling technique to 58 ASN in the Secretariat environment of Mahakam Ulu Regency. The data processing was carried out using the 3.0 SmartPls program. The first result showed that the employee engagement variable as the variable mediating the effect of talent management and employee capability, with partial mediation quality. Second, employee engagement is the variable mediating the effect of knowledge sharing and employee capability with partial mediation quality. This study confirmed that employee capability can be improved by improving the talent management and knowledge sharing. Employee engagement either technically or managerially may enhance the experience of the relevant employee by which through experience enhancement, the employee capability may also be improved. Theoretically, this study was expected to be able to enrich and complete the realm of science in the field of management science especially those related to human resources management. Organizations who wish to improve employee capability can implement talent management well, revive the culture of knowledge sharing as well as engaging employees in organizational activities either technically or managerially. Practically, the result of this study can be used by heads of governmental organizations to enhance their employees’ competency, so that they can be the employees who are capable of performing organizational activities productively and efficiently.Keywords: Talent Management, Knowledge Sharing, Employee Engagement, Employee Capability